A Review on Fungal Myocarditis: The Agents, Predisposing Factors and Treatments: Fungal Myocarditis - Amiri, Mehrnaz; Cheraghi, Mahdis; Lotfali, Ensieh (Novelty in Biomedicine, 2023)
Background and Aim: Myocarditis is an inflammatory disease of the heart muscle. It has many symptoms, from mild chest tenderness to cardiogenic alarm. Fungal myocarditis is a disseminated infection that mostly occurs in immunocompromised patients, especially in the intensive care unit (ICU). It has similar symptoms to coronary disease. The exact diagnosis of fungal myocarditis is complex and may be caused by different fungal agents. Materials and Methods: A review of the literature on fungal myocarditis using PubMed and Google Scholar was conducted. This review collected case reports of fungal myocarditis from 2010 to 2023 worldwide to provide current prevalence in different sex categories and ages. Case reports were reported from North America, Asia, and Europe. Results: According to results, Aspergillus myocarditis was more commonly reported in men (71.4 %) and had the highest mortality rate among the other fungi (close to 57%). Generally, there are no case reports from South America, Africa, and Australia. Amphotericin B is the first drug choice for Aspergillus myocarditis. Despite qualifying voriconazole treatment, voriconazole use is still under research and has not been confirmed for childcare. Fungal myocarditis mainly occurs in immunocompromised patients who have been hospitalized in ICU. Conclusion: Regarding morbidity and mortality rate, myocarditis is an alarming disease. Misinterpreting signs and symptoms with other diseases often make diagnosing this disease complex. Delayed diagnosis often leads to failure of the multiple organs and can directly affect the treatment protocol.